Behavioural response to abusive supervision among hotel employees: The intervening roles of forgiveness climate and helping behaviour - Eluwole, Kayode K.; Ukeje, Uchechukwu Edwin; Saydam, Mehmet Bahri; Öztüren, Ali; Lasisi, Taiwo Temitope (John Wiley and Sons Inc, 2022)
The current study draws on conservation of resource theory to propose a research model in which forgiveness climate mediates the influence of abusive supervision on employees’ voice behaviour, helping behaviour, and customer-centric organisational citizen behaviour (OCB). Data gathered from hotel employees and their co-workers in Nigeria were used to assess the hypothesised associations. These relationships were assessed using structural equation modelling. The results indicated that abusive supervision reduces employees’ perception of forgiveness climate, helping behaviour, and customer-centric OCB and fosters voice behaviour. On the other hand, forgiveness climate erodes voice behaviour and heightens helping behaviour and customer-centric OCB. This study explains the theoretical and practical contribution of the findings. © 2022 John Wiley & Sons Ltd.
Keywords: behavioral response; consumption behavior; hotel industry; structural change; Nigeria